Relation between CYP2D6 genotype, personality, neurocognition and overall psychopathology in healthy volunteers. (July 2009) - Peññas-LLedóó, Eva M; Dorado, Pedro; Pacheco, Rodrigo; Gonzáález, Idilio; LLerena, Adriáán
Aims: A lower serotonin/higher dopamine tone in CYP2D6 poor metabolizers (PMs) versus extensive metabolizers (EMs) has been postulated, which is consistent with our prior research showing behavioral traits related to anxiety and impulsivity in PMs. This tone could also be related to PMs vulnerability to cognitive functioning and/or psychopathology. Therefore, the present study aimed to analyze the relationship between CYP2D6 genotype and personality, cognition and psychopathological vulnerability. The influence of affective state in these relationships was also analyzed.Materials & methods: A total of 144 healthy volunteers from the University of Extremadura (Spain) were evaluated by CYP2D6 genotypes, overall psychopathology (Symptom Checklist-90-revised [SCL-90-R]), personality (Karolinska Scales of Personality [KSP] and Temperament and Character Inventory [TCI-R]) and on cognitive functions with computerized CANTAB ®® tests.Results: PMs (n = 11) versus EMs (n = 133) (Mann––Whitney U-tests) presented higher ''impulsivity'' in both KSP and TCI-R, and better performance of sustained attention (on the Rapid Visual Information Processing test) and lower overall psychopathology with all PMs scoring below 0.7 on SCL-90-R (''positive affect'' group). There were differences between all participants scoring below (n = 107) and above (n = 37) 0.7 on SCL-90-R in most personality measures. Comparisons between PMs (n = 11) and EMs (n = 96) with SCL-90-R less than 0.7 maintained those results for KSP and CANTAB but also yielded greater scores on the TCI-R-''perfectionism'' subscale in PMs. In multivariate analyses controlled for age, sex and psychopathology, KSP-impulsiveness, CANTAB-sustained attention, spatial working memory and paired associate learning were significantly different in PMs versus EMs.Conclusion: In the studied population of healthy volunteers, PMs versus EMs showed lower vulnerability to psychopathology and greater impulsivity. Moreover, differences in neurocognition were found. The cross-study reproducibility of the relationship between CYP2D6 and personality may be difficult due to the influence of psychopathology among other factors. The personality and cognitive factors found in PMs appear compatible with a low serotonin/high dopamine balance.